The Effect Of Work Experience, Work Climate, And Work Ability To Employee Performance (Case Study At Pt. Toyo Kanetsu Indonesia) - Vithra, Muhammad Afdhal Vithra; Mursal, Mursal; Suhardis, Adnan Suhardis (Zona Manajerial: Program Studi Manajemen (S1), 2021)
This study aims to determine the effect of work experience, work climate, and work ability on employee performance (Case Study at PT. Toyo Kanetsu Indonesia). The method used is quantitative method. The population in this study were employees of PT. Toyo Kanetsu Indonesia 200 employees. The sample used is 100 respondents. The data collection technique used in this study was through an online questionnaire. The data analysis technique in this study uses Multiple Linear Regression using SPSS software version 25. The results of this study indicate that work experience has a positive and insignificant effect on employee performance at PT. Toyo Kanetsu Indonesia with a probability value of 0.305 > 0.05. Work climate has a positive and significant effect on employee performance at PT. Toyo Kanetsu Indonesia with a probability value of 0.000 > 0.05. Work Ability has a positive and significant effect on employee performance at PT. Toyo Kanetsu Indonesia with a probability value of 0.000 < 0.05. The coefficient of determination value of 86.5% shows the contribution of work experience, work climate and work ability to employee performance at PT. Toyo Kanetsu Indo nesia and the remaining 13.5% are explained by other variables.